(5-Aminoisophthalato-kappa N)triaqua(1,10-phenanthroline-kappa N-2,N `)cobalt(II) trihydrate - Zhang, Kou-Lin; Diao, Guo-Wang; Ng, S.W. (International Union of Crystallography, 2010)
The Co-II atom in the title compound, [Co(C8H5NO4)(C12H8N2)(H2O)(3)]center dot 3H(2)O, is six-coordinated in a CoN3O3 octahedral geometry; the water-coordinated Co-II atom is chelated by the N-heterocycle. An intermolecular N-H center dot center dot center dot O hydrogen bond occurs. The carboxylate entity coordinates through the amino group. The carboxylate donor unit, coordinated and uncoordinated water molecules interact through O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds, generating a tightly-held three-dimensional cage-like network.